Structure and surface morphology of mercury modified selenium thin films - Рубіш, В. М.; Грещук, О. М.; Дуркот, М. О.; Макар, Л. І.; Мудрий, С. І.; Пісак, Р. П.; Соломон, А. М.; Штаблавий, І. І.; Юхимчук, В. О.; Ясінко, Т. І. (Інститут проблем реєстрації інформації НАН України, 2023)
The results of investigations of the structure and surface morphology of nominally pure, crystallized and mercury modified amorphous selenium films are presented. Amorphous Se films with a thickness 500-1000 nm were obtained by vacuum evaporation of vitreous selenium from quasi-closed effusion cells on to unheated glass substrates. Crystallization of amorphous Se films was performed by their heating to a temperature of 423 K at a heating rate 6 K/min on air. Selenium films modification was carried out in special hermetic boxes by keeping them in mercury vapor for 0.5-168 hours at 283-293 K. The structure of the films was studied by the X-ray diffractometry and Raman spectroscopy methods. For the investigations of the surface morphology of modified selenium films a field emission scanning electron microscopy (FESEM) analysis was performed. It was established that the matrix of the amorphous Se film is a mixture of Se8 ring fragments and Sen chains, and the structure of the crystallized film corresponded to the structure of trigonal selenium. Exposure of the films in mercury vapor leads to the formation in the amorphous matrix the HgSe crystalline inclusions in the cubic modification, which accompanied by the appearance on the diffractograms and Raman spectrum of weakly expressed corresponding reflexes and bands. As the exposure time increases, the reflexes become pronounced, and their position agrees well with the position of intense reflexes on the diffractograms of crystalline mercury selenide obtained by the hydrochemical methods. Weakly expressed reflexes, characteristic of HgSe, were also detected in the diffractogram of mercury modified crystallized selenium film. FESEM studies of mercury modified selenium films confirm the conclusion based on the structural investigations that the phase structure formed during the modification of selenium films corresponds to the structure of crystalline mercury selenide.